Lesson Study: Improving Madrasah Teachers’ Ability in Writing a Scientific Paper in Banten - Yudi Juniardi; Irmawanty Irmawanty; Tazkia Aghnia Aulia (Universitas Negeri Padang, 2021)
This study aims to describe the lesson study mentoring activities carried out by the Teacher work Group (KKG) in improving the writing skills of madrasah teachers' scientific papers. There are three research questions: the first, What is the role of KKG in improving madrasah teacher's scientific paper writing skills?, the Second, What are the teacher's obstacles in writing a scientific paper?, and the last, How is the effectiveness of the Lesson Study (LS) carried out by the KKG in improving the writing skills of Ibtidaiyah Madrasah teachers?The subject of this research is lesson study activities which are held in two districts/cities: Tangerang and Serang City. Qualitative research methods were used in this study to describe the LS assistance carried out by the KKG in improving the writing skills of madrasah teachers' scientific papers. In collecting data used interview instruments, questionnaires, observations, and documentation. The results of this study concluded that the implementation of lesson study held at the KKG in Tangerang City and Serang City run well and was effective in improving teachers’ ability to write scientific papers. This assistance is carried out by involving madrasah supervisors and the Banten Province Madrasah Development Center. In addition, the teacher gave a positive response to the lesson study of scientific writing carried out at the KKG. Most of the teachers wereoptimistic that this lesson study of scientific writings can improve their knowledge and ability in writing, besides that they hope to get assistance to publish scientific papers both presented in scientific activities and scientific journals.